Aktivitas Peroksidase Mutan Pisang Kepok dengan Ethyl Methane Sulphonate (EMS) secara In Vitro 1 - Yanti, Yulmira (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
The activity of peroxidase were observed in leave of banana clone Kepok resulting by treatments EMS. The phenotype of peroxidase wasanalyzed from the banana clones resulting the induced by EMS and without induction after inoculated with pathogen Banana Blood deasesBacterium (BBD). The objectives of research are know variation of activity and band pattern of peroxidase. Induced mutation treatmentsconsist of control, 0.2% EMS for 1 and 3 hours, 0.5% for 1 and 3 hours, each treatments was provided five banana clones. The result showedthat variant value and coefisien variant of peroxidase activity in leaf tissue of clone treated by EMS increased compare to the control. Avariant control is 0.28 with coefisien variant is 29.92%, while variant value of treatment is 8.45 with coefisien variant is 75.75%.Appearance of peroxidase bands on clone resulting by EMS treatments were emerged four band pattern. The first and control band patternhas relative migration distance is 20 and 30, the second 15, 40 and 60, the third is 15, 35 and 50. There are four bands with different relativemigration distance that indicated polymorphic.